Editorial from Editor-in-Chief - Tamang, Bibek (International Journal on Engineering Technology, 2024)
25th April, 2024 Dear Esteemed Colleagues, Contributors, and Distinguished Readers, It is with great pride that I announce the release of the Special Issue of the International Journal on Engineering Technology (InJET), featuring the KEC Conference 2024 Proceedings, Volume VI. As the Editor-in-Chief of InJET, I extend my warmest greetings to all participants who have contributed to this scholarly endeavor. The theme of our conference, “Dedicated to Enhance Research Ability,” underscores the pivotal role of research in shaping the future of engineering and technology. Our commitment to fostering collaboration and advancing knowledge has been unwavering. The KEC Conference, now in its 6th Edition, continues to be a beacon for students, academicians, and researchers worldwide. This year, we have delved into various engineering and IT domains, including Civil Engineering, Computer Science, Electrical Engineering, Mechanical Engineering, Information Technology, and Electronics Engineering. Within this volume, you will find 29 meticulously reviewed research papers, authored by passionate individuals who share our vision for excellence. These papers have been scrutinized by national and international experts, ensuring their quality and relevance. I extend my heartfelt gratitude to our diligent reviewers, whose critical insights have elevated the caliber of these proceedings. Their dedication to maintaining academic rigor has been instrumental in our international recognition. In addition to the main conference, we hosted a Symposium on Traffic and Transportation Engineering in collaboration with the Society of Transport Engineers Nepal (SOTEN) and Safe & Sustainable Travel Nepal (SSTN). These symposiums provided a platform for in-depth discussions and innovative solutions in their respective fields. I would like to acknowledge our esteemed partners and sponsors: TechAxis, Thoplo Machine, Evolve IT Hub Nepal, Broadway Infosys-Nepal, Deerwalk Training Center, Skill Spark, and Coding Technology. Their unwavering support has been pivotal in making this conference a resounding success. Lastly, I express my sincere gratitude to Kantipur Engineering College for entrusting us with the responsibility of organizing this prestigious event. Their unwavering commitment to academic excellence has been our guiding light. ______________ Dr. Bibek Tamang Editor-in-Chief 6th International Conference on Engineering and Technology KEC Conference 2024